Sustentabilidade urbana: avaliação da qualidade ambiental do setor central de Uberlândia-MG - Biziak, Lucas Dovigo (2017)
The growth of the world population, in cities, demands planning of the territory, searching for better environmental quality and life. There are data that can corroborate this information, but it is necessary to pay attention to the fact that there isn’t emergent evidence of slowing of the urban population, especially in less developed countries. The point is that these less developed regions have serious problems, as urbanization, which may even be called "uneven", caused by late industrialization of the outlying areas of the cities, which attract in general, rural populations. The speed with which this process occurs, combined with few or no coordinated policies and actions of urban development, aggravate the problems concerning the use and occupation of land. The central sector of the city of Uberlândia is shown as a promising area of study, since the research problem becomes clear when asked what the environmental quality level found, since what is seen is the lack of information, compelling data and joint procedures regarding the analysis of this and the resolution of recurring environmental problems caused by different sources, which are hardly solved due to the cross-sectional analysis and often without taking into account the attributes of the site. With the specific objectives of creating an Urban Environmental Quality Index, to map this and suggest measures that can improve it and how these could be carried out, the methodology implies in the stages of creation and valuation of indicators, generation of maps and use of the plug -in Easy AHP from the QGIS software, which resulted in an index and its representation in a final urban environmental quality map. The results are as follows: urban environmental quality of the sector was considered bad to regular; The three best neighborhoods were Fundinho, Centro and Daniel Fonseca; The indicators that had greater weight in the attenuation of bad quality were: density of green area, vegetation cover and sanitation. Through the analysis of the results, it was then suggested a greater attention to the distribution of income in the whole sector; priority investment in the neighborhoods of Brasil, Osvaldo Rezende and Nossa Senhora Aparecida regarding the improvement of the city's storm drainage, which reflects in several risk areas of flooding in these neighborhoods; in promoting history and culture; increase and improvement of green areas and vegetation cover; and the creation of a Municipal Urban Environmental Quality System, in which all Secretariats should feed with data so that the indicators were calculated in real time or with an appropriate seasonality to the resources of the Municipality, in order to rationalize the investments of scarce resources and improve their control by the City Hall and the population.